THE FORMATION AND DEVELOPMENT STAGES OF PLOT LYRICS - Dosimbetova, Abadan Aliyevna; Jalgasbayeva, Ayzada Abdullayevna (SCIENCE and SOCIETY, 2026)
This article discusses the formation and developmental stages of narrative lyric, a form of lyric poetry in fiction. Additionally, it analyzes the initial plot elements found in lyric poetry.
Keywords: fiction; epic; lyric; drama; plot; narrative lyric; plot element